Aplicación de yeso agrícola como secante en la cama de pollos de engorde en el cantón Santa Rosa - Quille Ochoa, José Guillermo (2012)
This study aimed to evaluate the effect of treatment ondrying bed with Yesolina chickens (commercial) this research was conducted November 7, 2011andculminatedJanuary 5, 2012. On Santa Rosa parish Piñas. The Advanced track, we worked with 240chickensfrom day to 56days of their respective sales, proceeded to build four warehouses of dimensions4m x3m60 bird seach, which were distribute din four homogeneous groups. treatments were applied according to the level of incorporation of the sulfate of calcium (0, 1, 2, 3%) in the bed of the chickens the same one that was applied during the studio, what process had the following objectives: To fulfill the first objective: "To evaluate the effect of the sulfate of calcium (Yesolina), as blotter of the bed it has more than enough in meat chickens, being considered the humidity and the detachment of the scent ammonia. To develop the second objective: 2. to analyze the sanitary incidence dares of the determination of ammonia. It was considered the percentage of mortality of the birds during the whole study process. To carry out the third objective: 3. to determine the economic feasibility of the chickens in relationship of use of this drying method. It was considered the expenditures that it embraced the investigation and the revenues that were obtained during the development of the same one. Parameters were analyzed weekly production of poultry and ammonia levels, pH of the bed moisture content of the bed, water consumption, feed intake, weight gain, mortality. We also assessed the consistency of the results lee. reached the following conclusions: Amount ofammoniawasobtainedlargelycontrol groupT0=5.32. Moisture frompoultry littershowedthe following averageT0= 30,T1=26.42, while theT3=21.6. WereneutralpH levelsbeing mostespeciallybajos.T3= 7.07, T2= 7.28followed. Feed intakewas higherT3=3.424g, and the lower consumptiontreatmentT0 =3.303gr. The weight gain, theexperimentalgroupscoredparticularlyT3=1.783g, and the lowest averagewasT0=1.637gr. Moreefficientfeed conversionwas obtainedinthetreatmentT3 =1.85. Asmortalityrateswere lowT0= 0.71, andT3=0.14. The most useful treatment obtained in T0 with $ 73.16; follows the less useful for treatment T01%: with $ 37.95.